Ultrathin Ni(0)‐Embedded Ni(OH)2 Heterostructured Nanosheets with Enhanced Electrochemical Overall Water Splitting - Dai, Lei; Chen, Zhe‐Ning; Li, Liuxiao; Yin, Peiqun; Liu, Zhengqing; Zhang, Hua (Advanced materials (Weinheim), 2020)
The efficiency of splitting water into hydrogen and oxygen is highly dependent on the catalyst used. Herein, ultrathin Ni(0)‐embedded Ni(OH)2 heterostructured nanosheets, referred to as Ni/Ni(OH)2 nanosheets, with superior water splitting activity are synthesized by a partial reduction strategy. This synthetic strategy confers the heterostructured Ni/Ni(OH)2 nanosheets with abundant Ni(0)‐Ni(II) active interfaces for hydrogen evolution reaction (HER) and Ni(II) defects as transitional active sites for oxygen evolution reaction (OER). The obtained Ni/Ni(OH)2 nanosheets exhibit noble metal‐like electrocatalytic activities toward overall water splitting in alkaline condition, to offer 10 mA cm−2 in HER and OER, the required overpotentials are only 77 and 270 mV, respectively. Based on such an outstanding activity, a water splitting electrolysis cell using the Ni/Ni(OH)2 nanosheets as the cathode and anode electrocatalysts has been successfully built. When the output voltage of the electrolytic cell is 1.59 V, a current density of 10 mA cm−2 can be obtained. Moreover, the durability of Ni/Ni(OH)2 nanosheets in the alkaline electrolyte is much better than that of noble metals. No obvious performance decay is observed after 20 h of catalysis. This facile strategy paves the way for designing highly active non‐precious‐metal catalyst to generate both hydrogen and oxygen by electrolyzing water at room temperature. Heterostructured Ni/Ni(OH)2 nanosheets synthesized using a partial reduction strategy are used as an efficient multifunctional electrocatalyst for the hydrogen evolution reaction, the oxygen evolution reaction, and overall water splitting. This work opens up new opportunities in the rational design of cost‐effective and highly efficient multifunctional electrocatalysts for renewable energy conversion.